THE MEDIATING EFFECT OF LIFESTYLE ON THE INFLUENCE OF COUNTRY OF ORIGIN AND FANATICISM ON CUSTOMER LOYALTY - Sophia Purnama Simanjuntak; Jenny Yulis Sara Azhari; Sarwoto; Willy Cahyadi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This research investigates the impact of experiential consumption in Tebing Tinggi City's culinary MSME industry, specifically focusing on the shift from traditional bamboo steamers (klakat) to cost-efficient alternatives. This transition risks eroding product authenticity and long-term customer loyalty. The study empirically analyzes the influence of Country of Origin (COO) and consumer fanaticism on customer loyalty, with lifestyle serving as a mediating variable. Using a descriptive quantitative approach, data were collected from consumers of five specialized dimsum outlets and analyzed via Structural Equation Modeling (SEM-PLS) using SmartPLS 3.8. The findings reveal that while COO and fanaticism positively and significantly influence lifestyle, their direct impact on customer loyalty is insignificant. Instead, the study confirms a full mediation effect, demonstrating that lifestyle is the critical bridge between these factors and loyalty. The novelty of this research lies in recontextualizing the COO variable—traditionally used in global manufacturing—to evaluate the physical attributes of regional culinary artifacts. Practically, the study recommends that MSME actors preserve traditional bamboo steamer elements as a strategic instrument to foster an active urban lifestyle ecosystem, thereby securing long-term consumer loyalty.